ANALISIS KOMPOSISI KIMIA DAN SIFAT ORGANOLEPTIK TEPUNG PISANG Ã¢â‚¬Å“MULU BEBEÃ¢â‚¬Â (Musa acuminata) DENGAN SUHU DAN WAKTU PENGERINGAN YANG BERBEDA - Ibrahim, Abu Rahmat; Albaar, Nurjanna (Universitas Khairun, 2020)
The present study aims to analyze the effect of temperature and drying time on chemical composition and organoleptic characteristics of